A Study to Assess the Prevalence and Risk Factors Regarding Postnatal Depression Among Postnatal Mothers in Postnatal Ward, MGM Hospital, Aurangabad (British Journal of Multidisciplinary and Advanced Studies, 2023)
Postnatal depression (PPD) affects women around the world and it is estimated that its prevalence runs at about 10-15%. Some studies show that postnatal depression may affect up to 30% of all women after delivery and has a significant impact on the mother and long term consequences on the cognitive and emotional development of children. The occurrence of postnatal depression can have serious consequences not only on the mother but also on the mother-infant bonding and indirectly hinder the psycho affective development of the child, hence it’s important to detect early. In long term untreated depression may lead to subsequent emotional, behavioral and cognitive problems for child.The present study was carried out in Mahatma Gandhi Hospital, Aurangabad, Maharashtra, among postnatal mothers admitted in postnatal ward. 100 postnatal mothers were the study participants out of which 45 were primipara and 55 were multipara. Prevalence was assessed using Standardized Edinburgh postnatal depression scale (EPDS) and risk factors were assessed using self-administered questionnaire.The study results showed Highest percentage (51%) was in age group of 18-23yrs. Majority of postnatal mothers (41%) have completed their primary education. Most of the (49%) postnatal mothers are homemaker. Majority of postnatal mothers (55%) were having family income 11,000-15,000. Most of the (67%) postnatal mothers were from joint family type. Majority of postnatal mothers (75%) were Hindu. Most of postnatal mothers (53%) were having 1-3 yrs of marriage duration. Around (58%) of postnatal mothers were from rural area. Most of the (48%) postnatal mothers have postpartum day of 4-6 days.The study results showed that majority of sample i.e. (60%) 60 postnatal mothers are having mild depression. (22%) 22 postnatal mothers are having moderate depression. (18%) 18 postnatal mothers are having severe depression. There is no significant association between risk factors and selected demographic variables and there is no significant association between prevalence and selected demographic variables